Manipulating Objects and Telling Words: A Study on Concrete and Abstract Words Acquisition - Borghi, Anna M.; Flumini, Andrea; Cimatti, Felice; Marocco, Davide; Scorolli, Claudia (Frontiers in Psychology, 2011)
Four experiments (E1-E2-E3-E4) investigated whether different acquisition modalities lead to the emergence of differences typically found between concrete and abstract words, as argued by the Words As Tools (WAT) proposal. To mimic the acquisition of concrete and abstract concepts, participants either manipulated novel objects or observed groups of objects interacting in novel ways (training1). In TEST 1 participants decided whether two elements belonged to the same category. Later they read the category labels (training2); labels could be accompanied by an explanation of their meaning. Then participants observed previously seen exemplars and other elements, and were asked which of them could be named with a given label (TEST2). Across the experiments, it was more difficult to form abstract than concrete categories (TEST 1); even when adding labels, abstract words remained more difficult than concrete words (TEST 2). TEST3 differed across the experiments. In E1 participants performed a feature production task. Crucially, the associations produced with the novel words reflected the pattern evoked by existing concrete and abstract words, as the first evoked more perceptual properties. In E2-E3-E4, TEST3 consisted of a color verification task with manual/verbal (keyboard-microphone) responses. Results showed the microphone use to have an advantage over keyboard use for abstract words, especially in the explanation condition. This supports WAT: due to their acquisition modality, concrete words evoke more manual information; abstract words elicit more verbal information. This advantage was not present when linguistic information contrasted with perceptual one. Implications for theories and computational models of language grounding are discussed.